2019
DOI: 10.1093/cid/ciz284
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus Among Pulmonary Tuberculosis Patients From 4 Tuberculosis-endemic Countries: The TANDEM Study

Abstract: BackgroundDiabetes mellitus (DM) increases active tuberculosis (TB) risk and worsens TB outcomes, jeopardizing TB control especially in TB-endemic countries with rising DM prevalence rates. We assessed DM status and clinical correlates in TB patients across settings in Indonesia, Peru, Romania, and South Africa.MethodsAge-adjusted DM prevalence was estimated using laboratory glycated hemoglobin (HbA1c) or fasting plasma glucose in TB patients. Detailed and standardized sociodemographic, anthropometric, and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
1
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 32 publications
7
79
1
13
Order By: Relevance
“…The risk of diabetes was the greatest in the middle-aged group (40-65 years). However, unlike recent data from a multi-country study investigating diabetes in TB (the TANDEM study), we did not observe an association between diabetes and previous TB or with smear positive cases 31 . The distribution of HbA1c values for our diabetic population (new and previously diagnosed cases) was also similar to that from the Indonesian TANDEM study population, in whom a single point of care (POC) HbA1c test was shown to have high sensitivity and specificity to detect new diabetes cases, adding confidence to our diagnoses of diabetes using this single POC measurement 41 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The risk of diabetes was the greatest in the middle-aged group (40-65 years). However, unlike recent data from a multi-country study investigating diabetes in TB (the TANDEM study), we did not observe an association between diabetes and previous TB or with smear positive cases 31 . The distribution of HbA1c values for our diabetic population (new and previously diagnosed cases) was also similar to that from the Indonesian TANDEM study population, in whom a single point of care (POC) HbA1c test was shown to have high sensitivity and specificity to detect new diabetes cases, adding confidence to our diagnoses of diabetes using this single POC measurement 41 .…”
Section: Discussioncontrasting
confidence: 99%
“…The prevalence of diabetes, at 9.1%, with more than 50% of diabetes cases newly diagnosed by the study screening was higher than current national estimates for the Philippines general population (6.1%,WHO 2016) 29 . but lower than the 14.1% reported in 634 urban HIV-negative Indonesians with newly diagnosed pulmonary TB, systematically assessed for diabetes by fasting blood glucose 30 and more recently of 19.7% in the Indonesian participants of the multi-country "TANDEM study" 31 . Previous limited reports in the Philippines include a diabetes prevalence of 18% in pulmonary TB patients in Quezon City (N = 38) 32 , and 17.7% in a cohort of acutely unwell admissions to a TB ward in Manila (N = 348) 33 .…”
Section: Discussionmentioning
confidence: 83%
“…A biomarker study to examine the influence of helminth co-infection in leprosy patients is currently ongoing. Moreover, the influence on biomarker levels of co-morbidities, such as diabetes mellitus which is known to increase the risk of active TB ( 42 ), on the disease outcome should be further studied. Another issue impeding straightforward implementation of biomarkers is that inflammatory markers are not disease-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, logistic regression models were applied to explore the risk factors of primary drug resistance among TB-DM cases as well. Covariates adjusted for multivariable models were chosen based on previous studies 4,11. Factors including age, sex (male or female), BMI, drinking (yes/no), smoking (yes/no), cavity (yes/no)m and hypertension (yes/no) were adjusted for multivariable logistic regression model.…”
Section: Methodsmentioning
confidence: 99%